1977
DOI: 10.2307/134466
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Prices in the Global Corporation under Internal and External Constraints

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Rather, it adjusts the TP only until the high-tax division earns zero profit. Booth and Jensen (1977) show that the TP becomes determinate when top management, in general, constrains itself to meet minimum profit levels in each country.…”
Section: Cdm: the Modified Horst (1971) Solutionmentioning
confidence: 99%
“…Rather, it adjusts the TP only until the high-tax division earns zero profit. Booth and Jensen (1977) show that the TP becomes determinate when top management, in general, constrains itself to meet minimum profit levels in each country.…”
Section: Cdm: the Modified Horst (1971) Solutionmentioning
confidence: 99%
“…Rather, the transfer price adjusts only until the high-tax division earns zero profit. Booth and Jensen (1977) show that the transfer price becomes determinate when top 1 P 12 P management constrains itself to meet minimum profit levels in each country.…”
Section: The Core Literaturementioning
confidence: 98%
“…Booth and Jensen (1977) note that the transfer price is arbitrary and indeterminate when top management's profit-maximizing objective is unconstrained, such as by an arm's length constraint (p. 434). Schjelderup and Sørgard (1995) impose an internal profit constraint to ensure a determinate solution.…”
Section: The Core Literaturementioning
confidence: 99%
“…His main result was that the MNF will maximize its post-tax global profits by charging either the highest or the lowest possible transfer price, depending on the relative levels of the tariff and the tax differentials. A number of theoretical studies dealing with transfer pricing, Booth and Jensen (1977) and Itagaki (1979) amongst others, assume that the values of the upper and lower limits on the transfer prices are exogenously determined by government regulations. Eden (1983Eden ( , 1985 and Samuelson (1982) showed that, in the presence of non-constant costs and imperfect competition, conditions likely to be encountered by MNFs, the actual value of the transfer price limits are endogenously determined by the firm's output and trade decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The parent division and the subsidiary both produce the final good and the intermediate good. The monopoly assumption is adopted to simplify the analysis and is quite standard in the literature (e.g., Booth and Jensen, 1977;Copithorne, 1971;Eden, 1983Eden, , 1985Horst, 1971;Samuelson, 1982). The underlying cost structures are assumed to be such that the parent firm exports the final good and the intermediate good to the subsidiary.…”
Section: Introductionmentioning
confidence: 99%